2016
DOI: 10.3346/jkms.2016.31.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Mortality in Population of Patients with Paroxysmal Nocturnal Hemoglobinuria (PNH): Results from a Korean PNH Registry

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a progressive, systemic, life-threatening disease, characterized by chronic uncontrolled complement activation. A retrospective analysis of 301 Korean PNH patients who had not received eculizumab was performed to systematically identify the clinical symptoms and signs predictive of mortality. PNH patients with hemolysis (lactate dehydrogenase [LDH] ≥ 1.5 × the upper limit of normal [ULN]) have a 4.8-fold higher mortality rate compared with the age- and sex-matched g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 20 publications
2
84
0
1
Order By: Relevance
“…In the only double‐blind, randomised, placebo‐controlled trial of eculizumab in 87 patients with PNH (Hillmen et al , ), serious nonmeningococcal infections were reported in similar proportions of eculizumab‐treated and untreated patients with PNH (2% vs. 6%, respectively). Outside of the clinical trial programme, severe infections have been reported in up to 18% (Nishimura et al , ) and were identified as the cause of death in 25–40% of mortalities reported in untreated patients with PNH (Jang et al , ; Yu et al , ). Infections have been identified as precipitating events in patients with aHUS (Noris et al , ; Schifferli et al , ; Geerdink et al , ; Fremeaux‐Bacchi et al , ; Campistol et al , ); it is important to note that immunosuppression may play a role in these infections because many aHUS patients receive dialysis or renal transplantation (Noris et al , ; Schifferli et al , ; Geerdink et al , ; Fremeaux‐Bacchi et al , ; Lok & Foley, ; Campistol et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the only double‐blind, randomised, placebo‐controlled trial of eculizumab in 87 patients with PNH (Hillmen et al , ), serious nonmeningococcal infections were reported in similar proportions of eculizumab‐treated and untreated patients with PNH (2% vs. 6%, respectively). Outside of the clinical trial programme, severe infections have been reported in up to 18% (Nishimura et al , ) and were identified as the cause of death in 25–40% of mortalities reported in untreated patients with PNH (Jang et al , ; Yu et al , ). Infections have been identified as precipitating events in patients with aHUS (Noris et al , ; Schifferli et al , ; Geerdink et al , ; Fremeaux‐Bacchi et al , ; Campistol et al , ); it is important to note that immunosuppression may play a role in these infections because many aHUS patients receive dialysis or renal transplantation (Noris et al , ; Schifferli et al , ; Geerdink et al , ; Fremeaux‐Bacchi et al , ; Lok & Foley, ; Campistol et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Paroxysmal nocturnal haemoglobinuria (PNH) and atypical haemolytic uraemic syndrome (aHUS) are rare, chronic, diseases that may be life‐threatening without treatment (Brodsky, ; Jang et al , ; Loschi et al , ; Fakhouri et al , ). Both diseases are caused by uncontrolled complement activation, resulting in intravascular haemolysis in PNH and systemic thrombotic microangiopathy (TMA) in aHUS (Noris & Remuzzi, ; Brodsky, ).…”
mentioning
confidence: 99%
“…This is an important finding as several studies have identified LDH ≥ 1.5 × ULN as an independent prognostic factor in PNH. 3,20 Clinical symptoms, such as those that define HDA, further aggravate this negative prognostic predictor.…”
Section: Discussionmentioning
confidence: 99%
“…1 The clinical manifestations of PNH are thromboembolism (TE) driven by intravascular hemolysis and bone marrow (BM) failure. [2][3][4][5][6] Although eculizumab, a humanized monoclonal antibody directed against complement component C5, has been increasingly used to control intravascular hemolysis in patients with hemolytic PNH, this treatment does not improve BM failure. 7,8 Moreover, patients with PNH frequently exhibit an element of BM failure such as aplastic anemia (AA), 5,9 and about half of all patients with AA have been found to have a detectable population of PNH clones.…”
Section: Introductionmentioning
confidence: 99%